2015
DOI: 10.1002/2015wr017323
|View full text |Cite
|
Sign up to set email alerts
|

Climate and agricultural land use change impacts on streamflow in the upper midwestern United States

Abstract: Increased streamflow and its associated impacts on water quality have frequently been linked to changes in land use and land cover (LULC) such as tile drainage, cultivation of prairies, and increased adoption of soybeans (Glycine max) in modern day cropping systems. This study evaluated the relative importance of changes in precipitation and LULC on streamflow in 29 Hydrologic Unit Code 008 watersheds in the upper midwestern United States. The evaluation was done by statistically testing the changes in slope a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
163
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(174 citation statements)
references
References 27 publications
10
163
1
Order By: Relevance
“…With regard to the criticism on the robustness of our methodology, we would like to point out that Gupta et al [2015] used a statistical technique to test whether or not prechange and postchange streamflow versus precipitation relationships are the same or different. Our conclusion was that the shape of the relationship has not changed drastically for most watersheds and higher flows in postchange period are mainly due to higher precipitation (5 year moving average plots).…”
Section: 1002/2016wr018926mentioning
confidence: 99%
See 4 more Smart Citations
“…With regard to the criticism on the robustness of our methodology, we would like to point out that Gupta et al [2015] used a statistical technique to test whether or not prechange and postchange streamflow versus precipitation relationships are the same or different. Our conclusion was that the shape of the relationship has not changed drastically for most watersheds and higher flows in postchange period are mainly due to higher precipitation (5 year moving average plots).…”
Section: 1002/2016wr018926mentioning
confidence: 99%
“…Using the 5 year moving averages, Gupta et al [2015] showed that increased flows in the postchange period are mainly clustered at higher precipitation levels with the general relationship between streamflow versus precipitation nearly the same. Also, these authors showed that annual ET has remained the same [Gupta et al, 2015, Tables S3 and S4] (Sen's slope was not significant at P 5 0.05) for all agricultural watersheds for the period of streamflow records. Gupta et al [2015] further explored the underlying reason for a constant ET between the prechange and postchange periods by comparing the ET of present and previous crops; lakes, ponds, depressions, and pan evaporation; as well as differences in consumptive use by hay before and after LULC changes.…”
mentioning
confidence: 99%
See 3 more Smart Citations